(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The antitumor agent cisplatin and progesterone separate and joint action on content of total phospholipids and their individual fractions in nuclei from rat thymus cells were investigated. When used separately, cisplatin and progesterone exhibit its own distinctive properties. Cisplatin reduces, and progesterone, on the contrary, increases the content of total phospholipids. When used together, the effects of these drugs are summed up. Thus total phospholipid content of rat thymus cell nuclei increases by 17% after the joint injection of cisplatin and progesterone. These changes have different effects on quantities of individual phospholipid fractions. It is assumed that the effects of cisplatin and progesterone, both in their separate and joint action, can be mediated by quantitative changes in internuclear lipids that in turn can regulate the main functions of the cell nuclei.